2020
DOI: 10.1088/2515-7620/ab915e
|View full text |Cite
|
Sign up to set email alerts
|

Use of alternative water sources in irrigation: potential scales, costs, and environmental impacts in California

Abstract: Under the risk of drought, unreliable water supplies, and growing water demand, there is a growing need worldwide to explore alternative water sources to meet the demand for irrigation in agriculture and other outdoor activities. This paper estimates stocks, production capacities, economic costs, energy implications, and greenhouse gas (GHG) emissions associated with recycled water, desalinated brackish and seawater, and stormwater in California, the largest US state and the most significant fresh and processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Furthermore, alternative water sources, such as recycled water, brackish water, seawater, and storm water, have been used for irrigation in various parts of the world and for a variety of purposes, including irrigating agricultural crops. Such examples from the current and previous studies showed the challenges associated with higher salinity water irrigation in general, and those which negatively affect wheat crops in particular ( Qin and Horvath, 2020 ; Dolan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, alternative water sources, such as recycled water, brackish water, seawater, and storm water, have been used for irrigation in various parts of the world and for a variety of purposes, including irrigating agricultural crops. Such examples from the current and previous studies showed the challenges associated with higher salinity water irrigation in general, and those which negatively affect wheat crops in particular ( Qin and Horvath, 2020 ; Dolan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
“…Due to the global shortage of freshwater for irrigation, brackish water is often used in orchards, including avocado 50 , 51 . Using low-quality water for sprinkling might damage the foliage and decrease the final yield 52 .…”
Section: Discussionmentioning
confidence: 99%
“…With layered uncertainty characterizing future water supply and demand on the Monterey Peninsula, more information is needed before the region can confidently plan a permanent water solution. Alternative water supplies require greater cost, energy, and emissions compared to conventional surface and groundwater sources [87], so planning efforts must consider the best balance between conventional and alternative supplies, in addition to the right portfolio of alternative supplies [88]. Uncertainty surrounding Monterey's water demand stems partly from the recent decline in water demand within CalAm's service area, which fell from 16.3 million m 3 /y (13,200 AFY) in 2009 [36] to 11.4 million m 3 /y (9200 AFY) in 2019 [89].…”
Section: Planning Supply For Uncertain Demandmentioning
confidence: 99%